Use of the Equivalent Mining Height Method for Understanding Overlying Strata Movement and Stress Distribution in an Isolated Coal Pillar - Yang Chen; Dong Li; Fuxing Jiang; Lili Zhang; Cunwen Wang; Sitao Zhu (Shock and Vibration)
In order to study the changing rules of displacement filed and stress field of overlying strata on isolated pillar with filling mining method, a self-designed model of isolated pillar with an equivalent mining height and a monitoring system of stress is employed to study the progressive failure of overlying strata and the changing rules of induced displacement and stress, as the equivalent mining height increases. The findings from the trial tests show the following: (1) When the equivalent mining height is small, the overlying strata on the isolated coal pillar only bend and subside, but the overlying strata located on the goafs of two sides remain stable. (2) As the equivalent mining height increases, the degree of stress concentration on section coal pillar will rise and produce plastic failure in the first place near large caving goaf. The strata can subside between isolated working face and adjacent large caving goaf. (3) As the equivalent mining height increases further, new cracks in the roof of isolated working face will unite the cracks of carving goaf on two sides in horizontal direction, leading to a significant rise of the height of cracks. Three goafs will evolve into a large carving goaf, and the vertical cracks on the outer side of the carving goaf intersect with one another to form “fracture band”. The research acquires the key points for prevention in mining the isolated coal pillar with filling method and provides guidelines to implement this technique and to prevent rock burst.